2023
DOI: 10.1017/jfm.2022.1037
|View full text |Cite
|
Sign up to set email alerts
|

An electrohydrodynamic dance of unequal partners

Abstract: The dynamics of charge-free dielectric droplets under electric fields in weakly conducting fluids is relevant to a large range of technological and environmental applications. In Sorgentone & Vlahovska (J. Fluid Mech., vol. 951, 2022, R2), the authors investigate by asymptotic theory and boundary integral simulations the motility states of a pair of dissimilar droplets at an arbitrary orientation to the electric field and find a state of steady motility that is carefully balanced between repulsion and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Recent work has demonstrated that two dissimilar drops may undergo non-reciprocal EHD interactions, 27 via theoretical calculations 50 and boundary integral simulations. 51 While pairwise DEP interactions are always reciprocal, since the polarization of each drop contributes equally to the relative motion of the pair, hydrodynamic interactions due to the EHD flow depend only on the properties of the drop instigating the flow.…”
Section: Bidisperse Emulsionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has demonstrated that two dissimilar drops may undergo non-reciprocal EHD interactions, 27 via theoretical calculations 50 and boundary integral simulations. 51 While pairwise DEP interactions are always reciprocal, since the polarization of each drop contributes equally to the relative motion of the pair, hydrodynamic interactions due to the EHD flow depend only on the properties of the drop instigating the flow.…”
Section: Bidisperse Emulsionsmentioning
confidence: 99%
“…20,21 Observation of the individual and collective behavior of active drop systems can thus be difficult at long timescales, due to finite limitations in the fuel available. 27 Effort has also been made to design systems that undergo collective motion via external energy input, such as with electric and magnetic fields, [28][29][30][31][32] light, 33 or acoustics. 34 However, using external fields to drive force-free motion of drops, as opposed to rigid particles, has received less attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation